New Jersey Public School Racial Ethnic Enrollments and Dropouts, 1978-79. - New Jersey State Dept. of Education, Trenton; New Jersey State Dept. of Education, Trenton ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
This report consists of forty-four tables containing information (by county, district, and sex) on enrollment in and dropouts from New Jersey public elementary and secondary schools. Also presented for each section (enrollment and dropouts) is a summary of all-county figures that carries totals for the State. The racial/ethnic data contained in the report were abstracted from enrollment information collected in 1978 and from a study of dropouts from the 1977-78 school year. Racial/ethnic group categories utilized for collection and presentation of data are: white, black, Hispanic, American Indian/Alaskan Native, and Asian or Pacific Islander. (Author/GC)
ERIC Note: Prepared in cooperation with the Office of Equal Educational Opportunity. Some tables may be marginally legible due to broken print.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: American Indians; Asian Americans; Blacks; Dropout Characteristics; Dropouts; Enrollment; Ethnic Groups; Hispanic Americans; Minority Groups; School Districts; Sex; Tables (Data); Whites; New Jersey; Numerical/Quantitative Data